Peran Perempuan dalam Mewujudkan Ketahanan Ekonomi Keluarga Islami (Studi Kasus pada Pedagang di Kecamatan Kayangan Kabupaten Lombok Utara) - Dedi Suprianto; Titiek Herwanti; Muhammad Irwan (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2019)
This research was aimed to investigate the reason why women worked as traders, analyze the prosperity of women’s work and their family were observed by Islam perspective, and examine how Islam’s view about women who worked specifically at traders in Kayangan district North Lombok. The study used descriptive qualitative method. To collect the data, the researcher used observation, interview, and documentation. Reduction technique, data display, and drawing conclusion were used to analyze the data. The data validation were observation, diligence improvement, and triangulation. The result of the study were (1). Economic factor, because husband doesn't have constant occupation and income of her husband is low. Psychology factor, is preference each people certain want to help their fellow. Education factor which low, health, self-motivation is propulsion that come from informan theirself to join look for basic necessities of life and environment is wish to be like neighbor and can possess or buy goods like which neighbor has were the reasons why women work at traders in Kayangan district , (2). Based on the informers, their living were better and helpful rather than before, their life after they worked is better than before and their husband is helpful. Syariah maqashid have changed their prayer, soul, mind, property and off spring (3). There was different Islamic perspective on women as workers that the Islamic law permitted the women as workers. Keywords: women’s worker, traders, Economic Resilience, maqashid syari’ah.